2014
DOI: 10.1021/jm500317a
|View full text |Cite
|
Sign up to set email alerts
|

Matched Molecular Pair Analysis: Significance and the Impact of Experimental Uncertainty

Abstract: Matched molecular pair analysis (MMPA) has become a major tool for analyzing large chemistry data sets for promising chemical transformations. However, the dependence of MMPA predictions on data constraints such as the number of pairs involved, experimental uncertainty, source of the experiments, and variability of the true physical effect has not yet been described. In this contribution the statistical basics for judging MMPA are analyzed. We illustrate the connection between overall MMPA statistics and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 96 publications
0
73
1
Order By: Relevance
“…The curated dataset consisted of 571 chalcones, which were the subject for SAR analysis using matched molecular pairs (MMP, Figure 1) of analysis [59] that reveal changes in properties measured between structures with high similarity in this case, evaluated by MACCS keys descriptor [60] and Tanimoto coefficient (>0.7) [61] e.g. lost or gain of activity results of specific changes on structure by comparison between two structures [59,62]. …”
Section: Resultsmentioning
confidence: 99%
“…The curated dataset consisted of 571 chalcones, which were the subject for SAR analysis using matched molecular pairs (MMP, Figure 1) of analysis [59] that reveal changes in properties measured between structures with high similarity in this case, evaluated by MACCS keys descriptor [60] and Tanimoto coefficient (>0.7) [61] e.g. lost or gain of activity results of specific changes on structure by comparison between two structures [59,62]. …”
Section: Resultsmentioning
confidence: 99%
“…a tenth of a unit. From a medicinal chemistry standpoint that difference might be negligible [30]. Therefore, it is paramount to pay especial attention to the effect size in addition to the P values.…”
Section: Discussionmentioning
confidence: 99%
“…cut-off at 2 fold change). The interpretation of the relative property value change in the MMP analysis is also dependent on the experimental error [39], [40]. Commonly authors use e.g.…”
Section: Application and Limitationmentioning
confidence: 99%
“…By assuming different experimental errors Kramer et al showed how the minimum number of pairs necessary to achieve significance can be calculated, as they explained the difference between statistical significance and effect size estimation [21], [44]. Relevant experimental errors for public and industry SAR databases are nowadays published [21], [39].…”
Section: Application and Limitationmentioning
confidence: 99%